Tahap Kesediaan Komuniti Sekolah Terhadap Keberkesanan Program Pendidikan Asas Vokasional di Sekolah - Zainol @ Zainun, Nur Hazwani; Abdul Wahab, Jamalul Lail (Selangor Humaniora Review, 2018)
The readiness of school communities in receiving and implementing Basic Vocational Education (PAV) programme is a key determinant of the success or failure of the programme. This study was conducted to identify the readiness level of school communities towards the effectiveness of Basic Vocational Education (PAV) programme in schools. There are four factors involved in measuring the level of readiness of school communities, namely the direction of the programme, the readiness of teachers, the readiness of administrators and the challenges / problems faced by teachers in implementing PAV. This study used quantitative and qualitative methods involving 15 teachers teaching PAV subjects in three schools in Negeri Sembilan. The data obtained from the questionnaire were analyzed using Statistical Packages for Social Sciences (SPSS) version 22. In general, the findings indicated that the overall readiness level of school communities implementing PAV was high however, the deficiencies and weaknesses identified in this study indicated that implementation of PAV has yet to reach the expected objectives. The main challenges / problems faced by teachers in the PAV programme is financial problems. The findings of this study enabled parties involved in particular Ministry of Education (MoE) to take appropriate actions to ensure the effectiveness of the PAV programme as well as to help increase the level of readiness of school communities in its implementation. In conclusion, the school community's readiness is needed in realizing the objective of implementing the PAV programme.